İş kazasından doğan maddi tazminat ve hesaplanması - Taşkın, İrfan (My University, 2019)
İş sözleşmesinden doğan gözetme borcu kapsamında işveren, işçinin beden ve ruh bütünlüğünü korumakla yükümlüdür. Mevzuatımızda geniş bir şekilde düzenlenen işverenin bu yükümlülüğü mevzuatla sınırlı tutulmamıştır. Bu kapsamda işveren, mevzuatta öngörülmemiş olsa bile bilimin ve teknolojinin gerektirdiği her türlü işçi sağlığı ve iş güvenliği önlemini almak zorundadır. Ancak bu önlemler genellikle işverenler tarafından üretim hızı üzerinde bir yük olarak görülmekte ve maliyet kaygısı nedeni ile alınmamaktadır. İşçi sağlığı ve iş güvenliği önlemlerinin alınmaması nedeni ile meydana gelen iş kazası veya meslek hastalığı sonucu zarar gören işçinin ya da ölümü halinde hak sahiplerinin uğramış olduğu zararlardan öncelikle Sosyal Güvenlik Kurumu sorumludur. Bu kapsamda Kurumca işçiye ya da ölümü halinde hak sahiplerine gelir bağlanmaktadır. Ancak Kurumca bağlanan bu gelirler götürü nitelik taşıdığından genellikle zarara uğrayanların gerçek zararlarını tam anlamıyla karşılamamaktadır. Bu durumda işçi ya da ölümü halinde hak sahipleri Kurumca karşılanmayan zararlarının karşılanması için zarara neden olanlara başvurmaktadır.Çalışmamızda iş kazasından doğan maddi tazminat Yargıtay kararları çerçevesinde detaylı bir şekilde incelenmiştir. Bu kapsamda maddi tazminat hesabında kullanılan yöntemler Yargıtay içtihadı ve doktrin görüşleri ile birlikte ele alınmış, kısmen yargı kararları kısmen de uygulama ile şekillenen hesap unsurlarına ilişkin açıklamalarda bulunulmuştur. Ayrıca maddi tazminat hesabı için gerekli olan birçok faktörün varsayıma dayalı bir şekilde belirlenmesi nedeni ile uygulamada ortaya çıkan sorunlara dikkat çekilerek çözüm önerileri sunulması amaçlanmıştır.

The employer is obliged to protect the physical and mental integrity of the worker within the content of the employer’s liability arising from the labour contract. This obligation of the employer, which is broadly regulated in our legislation, is not limited to the legislation. In this scope, the employer has to take all kinds of occupational health and safety measures required by science and technology, even if not stipulated in the legislation. However, these measures, which are generally regarded by employers as a burden on the production rate, are not taken due to cost concerns.The Social Security Institution (SSI) is primarily responsible for the aggrieved worker or the right holders in case of worker’s death due to an occupational accident or an occupational disease caused by failure to take occupational health and safety measures. In this regard, the SSI endows the worker or the right holders in case of worker’s death. However, since these revenues covered by the SSI are lump sum payments, generally they do not fully meet the actual losses of the sufferers. In this case, the worker or the right holders in case of worker’s death apply to those who have caused the loss to compensate for their losses not covered by the SSI. In the thesis, material compensation arising from an occupational accident is examined in detail within the framework of the Supreme Court decisions. In this context, the methods used in the calculation of material compensation are discussed together with the Supreme Court practices and doctrines, and the explanations related to account elements which were partially shaped by the Supreme Court decisions and by the implementation are presented. Additionally, it is aimed to offer solutions to the problems arising from the implementation due to the fact that many factors which are necessary for the calculation of material compensation are determined hypothetically.
Keywords: Employers’ Liabilities Arising From Occupational Accident; İş Kazası; İş Kazasından Doğan Maddi Tazminat; İşçi Sağlığı ve İş Güvenliği Occupational Accident; İşverenin İş Kazasından Doğan Sorumluluğu; Maddi Tazminat; Material Compensation; Material Compensation Arising From Occupational Accident; Occupational Health and Safety